Enhancing the Competitiveness of MSMEs Through Halal Certification Counseling, NIB Registration, and Trademark Registration in Pagar Agung Sub-district, Walantaka District, Serang City - Basrowi; Dayurni, Popi; Mulyawan, Galuh; Jannah, Roikhatul; Andriani, Nepi; Nurlela (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This community service aims to improve the competitiveness of MSMEs in Pagar Agung Village by addressing low legal awareness through halal certification counseling, NIB registration, and trademark assistance. Method: The program involved MSME identification, counseling, technical assistance, and monitoring to support participants in completing business legality processes. Practical Application: Around 70% of participants began the registration processes, leading to improved consumer trust and market access. The program offers a replicable model for enhancing MSME competitiveness. Conclusion: The initiative increased legal awareness and had a positive impact on MSME growth. Continued support is needed to help all participants complete the legality process and remain competitive.